Bulk superconducting materials as a tool for control, confinement, and accumulation of polarized substances: the case of MgB2 - Ciullo, G.; Barion, L.; Contalbrigo, M.; Del Bianco, L.; Lenisa, P.; Spizzo, F.; Statera, M.; Tagliente, G. (Frontiers in Physics, 2024)
Providing strong magnetic holding fields while at the same time guaranteeing shielding from unwanted external fields is a key requirement for the accumulation, preservation, and transport of nuclear-polarized materials: it is a crucial achievement for its exploitation in fusion test facilities and particle physics. High-temperature bulk superconducting materials represent an innovative and promising solution, as they are easily machinable and can be cooled by a coldhead. This work considers a bulk MgB2 superconducting hollow cylinder, and the successful preliminary studies, performed by measuring trapped fields in the order of 1 T in its center, encouraged us to upgrade the prototype apparatus for deep insight and knowledge. The new system allows working at a lower temperature of 8 K, exchanging cylinders and returning to working conditions in 1 day, and mapping the transverse fields along the radial coordinate (in 11 mm) and along the symmetry axis (in 48 mm). Then, it allows us to find the proper geometry and the production procedure for its use in a fusion test facility. The commissioning of the upgraded system provides results already useful for polarized fusion fuel, for instance, as a holding field for recombined hyper-polarized molecules from the recombination of atomic polarized beams, and it also gives the possibility of investigating the use of MgB2 in polarized nuclear targets.